Managing Fluid Overload in Chronic Kidney Disease: A Nursing Case Report - Pitora, Tobi; Farisianah, Issy; Al Fatih, Hudzaifah; Okatiranti (Tanjungpura Journal of Nursing Practice and Education, 2026)
Background: Chronic kidney disease (CKD) is a major contributor to the global disease burden. Kidney failure can also lead to various other complications, such as swelling due to fluid retention, anemia, infections, cardiovascular disorders, cognitive impairment, and metabolic and endocrine disorders. Objective: To determine the effectiveness of rinsing with boiled water on thirst in kidney failure patients undergoing a fluid restriction program. Method: A case report on an 81-year-old woman with a medical diagnosis of stage IV chronic kidney disease in the Anggrek B Ward of the Bandung City General Hospital. The client complained of swelling in the lower extremities accompanied by pain in the upper abdomen. The swelling occurred due to excess fluid volume. The author established a focused diagnosis of hypervolemia. Implementation was carried out using an Evidence-Based Practice approach through the application of fluid restriction by rinsing the mouth with boiled water. Result: The analysis indicatedthat rinsing the mouth with boiled water is effective in reducing thirst in patients with chronic kidney disease, supports adherence to fluid restriction programs, and can be used as a self-care nursing intervention at home to alleviate symptoms of hypervolemia in patients with chronic kidney disease.